2015
DOI: 10.2174/1386207318666150915113549
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antitumor Activity, and Structure-activity Relationship of Some Benzo[a]pyrano[2,3-c]phenazine Derivatives

Abstract: A series of benzo[a]pyrano[2,3-c]phenazine derivatives with a wide range of substitutions at ring C of the benzophenazine were designed and synthesized using the one-pot, four-component domino reactions. The targeted compounds were evaluated for their antitumor activities against HCT116, MCF7, HepG2 and A549 cancer cell lines in vitro. The most active compound 6{1,2,1,9} featured the CN and p-dimethylamino phenyl substituents on γ-pyran structure on ring C. Significantly, compound 6{1,2,1,9} was found to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…TLC was conducted on silica gel 250 micron, GF254 plates with short-wavelength UV light for visualization. 1 H-and 13 C-NMR spectroscopic measurements were performed on a Bruker AV-300 or 400 NMR spectrometer, using TMS as internal references at 298 K, respectively. High-resolution mass spectra (HRMS) were recorded on an Agilent 6520B UPLC-Q-TOF mass spectrometer (Agilent Technologies, Santa Clara, CA, USA).…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…TLC was conducted on silica gel 250 micron, GF254 plates with short-wavelength UV light for visualization. 1 H-and 13 C-NMR spectroscopic measurements were performed on a Bruker AV-300 or 400 NMR spectrometer, using TMS as internal references at 298 K, respectively. High-resolution mass spectra (HRMS) were recorded on an Agilent 6520B UPLC-Q-TOF mass spectrometer (Agilent Technologies, Santa Clara, CA, USA).…”
Section: Generalmentioning
confidence: 99%
“…Recently, based on the strategy of molecular hybridization, our group successfully screened out pyran‐phenazine hybrid molecules CPUL129 and CPUL149 ( Figure 1) from the phenazine library established by us before [11–18] . These compounds could accumulate and sequester iron in lysosomes through interacting with iron and regulating the expression of proteins (IRP2, TfR1, ferritin) engaged in iron transport and strorage, eventually specifically inhibit the stemness of breast cancer cells through triggering ferroptosis [19] …”
Section: Introductionmentioning
confidence: 99%
“…These experimental data proved that cyan group played an important role in antiproliferative activity: 189 and 190, possessing a p-dimethylamino group and p-hydroxyl group, respectively, demonstrated some cytotoxic activity to HCT116 cell line, IC 50 of 0.22 µM and 15.32 µM, respectively; 189 showed cytotoxic activity against HepG2 cell line with IC 50 of 6.71 µM; 188-191 showed weak or no activity against MCF-7 and A549 cell lines. SAR studies showed that cyan group and p-dimethylamino group played a significant role in antiproliferative activity and resulted in the decrease of cytotoxic activity [79]. According to the report of Gao et al, Kale et al selected some 2-phenazinamines derivatives and further utilized computational methods to investigate their protein targets.…”
Section: Benzo[a]pyran[23-c]phenazine Derivativesmentioning
confidence: 99%
“…Phenazines are a large group of natural or synthetic nitrogen-containing heterocycle compounds, have been demonstrated to act as promising agents with antimalarial, anticancer, and antiplatelet activities [1][2][3]. Previously, the natural phenazine derivative, N-(2-hydroxyphenyl)−2phenazineamine (Figure S1A) extracted from marine actinomycete BM-17 showed potent cytotoxicity against several cancer cells [4].…”
Section: Introductionmentioning
confidence: 99%